2022
DOI: 10.1128/aac.01085-22
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Crushed Delayed-Release Posaconazole Tablets in Rhino-Orbito-Cerebral Mucormycosis

Abstract: A significant proportion of patients with Rhino-orbito-cerebral mucormycosis (ROCM) develop oroantral fistulas. Due to the unclear efficacy of crushed delayed-release posaconazole tablets (DRPT) via nasogastric tube in this group of patients, clinicians often use inferior alternatives like posaconazole suspension. In this prospective study, we report good plasma concentrations (median, 2,639 ng/mL; interquartile range [IQR], 1,690 to 3,575 ng/mL; and range, 1,004 to 4,835ng/mL) and complete cure and survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Posaconazole treatment of CAM has been associated with decreased in-hospital mortality [11 ▪ ]. Manesh et al [74] found that crushing delayed-release posaconazole tablets was associated with good plasma concentrations and outcomes in 19 patients with rhino-orbito-cerebral MCR [74].…”
Section: Treatment Of Mucormycosismentioning
confidence: 99%
“…Posaconazole treatment of CAM has been associated with decreased in-hospital mortality [11 ▪ ]. Manesh et al [74] found that crushing delayed-release posaconazole tablets was associated with good plasma concentrations and outcomes in 19 patients with rhino-orbito-cerebral MCR [74].…”
Section: Treatment Of Mucormycosismentioning
confidence: 99%
“…95,108 Therapeutic target attainment can be particularly challenging for the pediatric population, with a number of strategies reported to optimize therapy, including crushing delayed release tablets. [109][110][111][112][113] A dose-response relationship between posaconazole and most toxicities has not been found. 114 The exception is dosedependent pseudohyperaldosteronism, which manifests mainly in hypokalemia and hypertension.…”
Section: Posaconazolementioning
confidence: 99%
“…However, these targets remain controversial; 105–107 animal data suggest that substantially higher concentrations may be needed for optimal treatment of mold infections 95,108 . Therapeutic target attainment can be particularly challenging for the pediatric population, with a number of strategies reported to optimize therapy, including crushing delayed release tablets 109–113 . A dose‐response relationship between posaconazole and most toxicities has not been found 114 .…”
Section: Antifungalsmentioning
confidence: 99%
“…4,5 Given the difficulty achieving therapeutic C min with POS-S, especially in patients with enteral feeding tubes, poor nutritional intake, or critical illness, we welcomed the reported success of crushing POS delayed-release tablets (POS-DRT) for either enteral feeding tube or oral administration in adults. [6][7][8] Similar data in children are lacking.…”
Section: Introductionmentioning
confidence: 99%